Developing Quizizz-Based Smart Games Integrating Banyumasan Local Wisdom to Support Early Childhood Character Development - Nur Hafidz; Musyafa Ali; Ahmad Aji Jauhari Ma’mun; Sefti Wijayanti (Jurnal Caksana : Pendidikan Anak Usia Dini, 2025)
The rapid advancement of digital technology has not been fully integrated into early childhood character education, even though this stage is crucial for building moral values and personality. This study aimed to develop Smart Game Activities based on the Quizizz application incorporating Banyumasan local wisdom to instill values of honesty, discipline, self-regulation, and cooperation in early childhood. The research followed a quasi-experimental pretest–posttest design with nonequivalent groups (experimental group n = 15, control group n = 16) and applied purposive non-random sampling to ensure homogeneity across classes. Ethical clearance was obtained from the Institutional Review Board of Universitas Muhammadiyah Purwokerto (Approval No. UMP/EDU/2025/0412), and parental consent was secured for all participants. The developed product integrates child-friendly UI/UX features such as narrated audio instructions, large touchable buttons, and animated feedback icons to enhance engagement and accessibility. Expert validation from three specialists (media, early childhood character, and pedagogy) yielded an average score of M = 3.47 (very feasible), and the instrument reliability reached α = 0.872, indicating high internal consistency. Ten valid items were retained to measure children’s character indicators (honesty, discipline, self-regulation, and cooperation). Statistical analysis confirmed the assumptions of normality and homogeneity, with equivalent pretest results between groups (p = 0.889). Post-intervention, the experimental group achieved an average N-Gain of 75.34% (high category), significantly outperforming the control group’s 36.64% (medium category) with an independent t-test result of p < 0.001. These findings indicate that Quizizz-based Smart Game Activities effectively foster early childhood character through a culturally grounded, interactive, and ethically designed digital learning experience